Effects of feed intake on methane gas emission (Mongolian Journal of Agricultural Sciences, 2020)
Hydrid lams of Dorper x Native sheep weighted with 44.5-61.1 kg live were selected and divided into three experimental groups. Each experimental groups were fed by 50 percentages grass, 50 percentages of cereals and 50 percentages of mineral containing fees separately. Methane gas emission was measured from animal fed by pellets amounted 2.5 kg, 1.48 kg and 1.11 kg for first, second and third groups, respectively. During the study period, sheep extricated 6.65 liters, 5.05 liters and 1.78 liters of methane gas. The methane extraction was 24.1-71.8 percentage higher in first feeding groups compared to other two groups (P